Human Capital Strategy Implementation for Business Plan at Material Handling Rental Services Startup LogisMe - Mukhlis, Muhammad; Indradewa, Rhian; Hamdi, Edi; Sunaryanto, Ketut (Journal of Accounting and Finance Management, 2024)
Efficient logistics and warehousing operations heavily rely on effective material handling and cleaning processes. The utilization of equipment like lifting scissors, hand stackers, and forklifts is crucial for the safe and smooth movement of raw materials, finished products, and heavy cargo within these facilities. Nevertheless, the substantial financial outlay for such equipment presents a significant hurdle for businesses in this industry. Despite this capital-intensive challenge, the logistics and warehousing sector has witnessed substantial growth, primarily driven by the e-commerce surge ignited by the COVID-19 pandemic. The escalating demand for online shopping has exerted considerable pressure on supply chains, necessitating expanded warehousing and transportation infrastructure. Human Resource Planning (HRP) involves strategically allocating and optimizing human capital within an organization. This process aligns with short, medium, and long-term objectives by determining the necessary workforce to meet operational requirements. HR planning translates organizational goals into specific human resource targets, ensuring the availability of skilled personnel to support business operations. LogisMe has a flexibility of working style and hours which combines both offline and online / remote working styles empowered with virtual office and Employee Self Service (ESS). The company also supports for employees work-life balance and rewards.